2007
DOI: 10.1021/ac0620359
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Ultra-Thin-Layer Chromatography and Atmospheric Pressure Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry in Bioanalysis

Abstract: The feasibility of ultra-thin-layer chromatography (UTLC) and atmospheric pressure matrix-assisted laser desorption/ionization mass spectrometry (AP-MALDI-MS) for bioanalysis was studied with benzodiazepines as model substances in human urine. Two-dimensional (2D) UTLC was shown to be an efficient technique for the separation of benzodiazepines. Separations occurred in 4-12 min, and the separated compounds were identified by AP-MALDI-MS. The limits of detection with AP-MALDI-MS and AP-MALDI-MS/MS were in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 37 publications
0
22
0
2
Order By: Relevance
“…Ultra-thin layer chromatography (UTLC) can also be combined with MS. UTLC is performed on 10 lm non-particulate planar stationary phases. Claimed benefits encompass faster development (1-6 min) and less solvent consumption (1-4 mL) at a similar or slightly lower resolution than with HPTLC (Salo 2007;Salo et al 2007). Although--as far as we know--this technique has not yet been applied to natural products, it seems worthwhile to explore its usefulness in phytochemical analysis.…”
mentioning
confidence: 99%
“…Ultra-thin layer chromatography (UTLC) can also be combined with MS. UTLC is performed on 10 lm non-particulate planar stationary phases. Claimed benefits encompass faster development (1-6 min) and less solvent consumption (1-4 mL) at a similar or slightly lower resolution than with HPTLC (Salo 2007;Salo et al 2007). Although--as far as we know--this technique has not yet been applied to natural products, it seems worthwhile to explore its usefulness in phytochemical analysis.…”
mentioning
confidence: 99%
“…Many classes of compounds have so far been analyzed by TLC with direct on-plate (MA)LDI-MS detection, including dyes (Gusev et al, 1995a), products of various organic reactions (St Hilaire et al, 1998), metal complexes (Matsumoto et al, 2002), siderophores from bacterial samples (Hayen & Volmer, 2005), pharmaceuticals and their impurities (Mowthorpe et al, 1999;Crecelius et al, 2002Crecelius, Clench, & Richards, 2004a;Salo et al, 2007), peptides (Gusev et al, 1995a;Mehl & Hercules, 2000), proteins (Gusev et al, 1995b;Bakry et al, 2007), nucleotides (Isbell et al, 1999), polymers (Matsumoto et al, 1999), as well as gangliosides (Ivleva et al, 2004(Ivleva et al, , 2005Dreisewerd et al, 2005), glycosphingolipids (GSLs) (Guittard, Hronowski, & Costello, 1999;Distler et al, 2008), LAB-ON-A-PLATE & phospholipids (Fuchs et al, 2007;Rohlfing et al, 2007), stem cell lipids (Fuchs et al, 2008), and bacterial toxins (Meisen et al, 2009). An example is shown in Figure 20.…”
Section: On-plate Separationmentioning
confidence: 99%
“…Unfortunately, AP-MALDI possesses normally lower sensitivity than common high vacuum MALDI. Nevertheless, it was shown that AP-MALDI in combination with UTLC is sufficiently sensitive to detect benzodiazepines directly in human urine without the need of a major workup of the sample (Salo et al 2007). One interesting application is the investigation of changes of dyes during photo-aging, i.e., upon the light-induced bleaching process.…”
Section: Pharmaceuticalsmentioning
confidence: 99%